How Middle-Skilled Workers Adjust to Immigration: The Role of Occupational Skill Specificity - Damiano Pregaldini; Uschi Backes-Gellner (Institute of Labor Economics (IZA), 2023)
Our study explores the effects of immigration on the employment of native middle-skilled workers, focusing on how this effect varies with the specificity of their occupational skill bundles. Exploiting the 2002 opening of the Swiss labor market to EU workers and using register data on the location and occupation of these workers, our findings provide novel results on the labor market effects of immigration. We show that the inflow of EU workers led to an increase in the employment of native middle-skilled workers with highly specific occupational skills and to a reduction in their occupational mobility. These findings can be attributed to immigrant workers reducing existing skill gaps, enhancing the quality of job-workers matches, and alleviating firms' capacity restrictions. This allowed firms to create new jobs, thereby providing increased employment options for middle-skilled workers with highly specialized skills and reducing the need to change their occupations. This research provides novel insights on the impact of immigration on the labor market.
Keywords: J15; J24; J62; 330; migration; cross-border workers; occupational skill specificity